Association between the rapid shallow breathing index and extubation success in patients with traumatic brain injury - dos Reis, Helena França Correia (Associação Brasileira de Medicina intensiva, 2013)
OBJECTIVE: To investigate the association between the rapid shallow breathing index and successful extubation in patients with traumatic brain injury. METHODS: This study was a prospective study conducted in patients with traumatic brain injury of both genders who underwent mechanical ventilation for at least two days and who passed a spontaneous breathing trial. The minute volume and respiratory rate were measured using a ventilometer, and the data were used to calculate the rapid shallow breathing index (respiratory rate/tidal volume). The dependent variable was the extubation outcome: reintubation after up to 48 hours (extubation failure) or not (extubation success). The independent variable was the rapid shallow breathing index measured after a successful spontaneous breathing trial. RESULTS: The sample comprised 119 individuals, including 111 (93.3%) males. The average age of the sample was 35.0±12.9 years old. The average duration of mechanical ventilation was 8.1±3.6 days. A total of 104 (87.4%) participants achieved successful extubation. No association was found between the rapid shallow breathing index and extubation success. CONCLUSION: The rapid shallow breathing index was not associated with successful extubation in patients with traumatic brain injury.